Biomarkers and cell phenotypes in TB patients with minimal or persisting lung inflammation post-anti-TB treatment and ex-vivo atorvastatin immunomodulatory effects on M. tuberculosis-infected PBMC - Motaung, Bongani (Department of Pathology, 2025)
Unresolved lung inflammation post-anti-TB treatment necessitates the evaluation of additional host-directed therapies (HDT). Statins, recognized for their pleiotropic effects, show potential as immunomodulators to reduce post-TB lung inflammation. The ongoing StatinTB clinical trial utilizes a double-blind, randomized, placebo-controlled approach post-anti-TB treatment to assess the safety and efficacy of atorvastatin in reducing post TB lung inflammation. At the end of TB treatment, Mtb culture-negative participants were stratified into minimal (Arm A, Total Lung Glycolysis (TLG) < 50 SUV) or persisting (Arm B/C, TLG ≥ 50 SUV) lung inflammation using Positron Emission Tomography/Computed Tomography (PET/CT) scan. Arm B/C received atorvastatin (40mg/day) or placebo for 12 weeks, and this data remains currently blinded. Study participants were evaluated for hematological, biochemical, and inflammatory parameters where ALP, proBNP, vitamin D, and CRP showed significant increases in Arm B/C compared to Arm A at